Temporary city between emergency and recovery - Roberto Ruggiero (Agathón)
The housing emergency resulting from earthquakes or other natural disasters generally finds an initial response in temporary structures such as prefabricated houses and/or containers. The chronicles of recent and less recent disastrous events show how such structures – inadequate to implement an acceptable living quality, thought and designed as ‘emergency’ solutions – remain in place for a long time, which can also occupy the space of some decades, waiting for the reconstruction. Although the resulting housing disadvantage is enormous, the current management policies in the field of post-disaster emergency do not seem to have dealt with this transitional phase in an organic way. The paper presents the first results of a scientific-design research carried out at the School of Architecture and Design Eduardo Vittoria of Ascoli Piceno (SAAD) of the University of Camerino concerning the transformation of post-disaster first emergency settlements into temporary urban systems capable of reactivating social and productive dynamics.